Revitalization of library management to optimize literacy in SDN 1 Kunti Ponorogo - Isni Athul Milla; Siti Chamidah; Edi Santoso (Universitas Muhammadiyah Magelang, 2022)
In schools, libraries play a critical role in determining the academic climate. To optimize scientific activities, the library has been designed as a structured system with various purposes and functions. The library at SDN 1 Kunti, Ponorogo, on the other hand, has been unable to function properly. As a result, it is necessary to make efforts to reform the library's proper function. One of the suggested activities is the revitalization of library management in order to improve the school's literacy culture. This activity is part of a series of MBKM-related Kampus Mengajar program. Based on the activities carried out, it appears that the student literacy culture in schools is improving, allowing this revitalization program to run smoothly and on target.